Enhancing the Health-Promoting Effects of Tomato Fruit for Biofortified Food - Assunta Raiola; Maria Manuela Rigano; Roberta Calafiore; Luigi Frusciante; Amalia Barone (Mediators of Inflammation)
Consumption of tomato fruits, like those of many other plant species that are part of the human diet, is considered to be associated with several positive effects on health. Indeed, tomato fruits are an important source of bioactive compounds with known beneficial effects including vitamins, antioxidants, and anticancer substances. In particular, antioxidant metabolites are a group of vitamins, carotenoids, phenolic compounds, and phenolic acid that can provide effective protection by neutralizing free radicals, which are unstable molecules linked to the development of a number of degenerative diseases and conditions. In this review, we will summarize the recent progress on tomatoes nutritional importance and mechanisms of action of different phytochemicals against inflammation processes and prevention of chronic noncommunicable diseases (e.g., obesity, diabetes, coronary heart disease, and hypertension). In addition, we will summarize the significant progress recently made to improve the nutritional quality of tomato fruits through metabolic engineering and/or breeding.